2006
DOI: 10.1097/01.mco.0000171129.29278.26
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrition on ageing and disease

Abstract: Supplementation with vitamins has little effect on ageing/prevention of chronic diseases, but antiinflammatory molecules like polyphenols are more effective, especially when combined with reduced intake of calorie-condensed foods. The effect of probiotics on ageing needs further exploration. The effects of caloric restriction, proven effective in other species to control aging and prolong lifespan, have not been fully explored in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Microvascular and macrovascular damage, seen in diabetes, is attributed to the accumulation of AGEs in tissues, but it is also associated with atherosclerosis, Alzheimer’s disease, end stage renal disease, rheumatoid arthritis, sarcopenia, cataracts, and other degenerative ophthalmic diseases, Parkinson’s disease, vascular dementia and several other chronic diseases [16,17,18,19]. For instance, Bar et al have demonstrated differential increases of AGEs products in Alzheimer’s dementia and vascular dementia compared to controls [20].…”
Section: Implications For Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular and macrovascular damage, seen in diabetes, is attributed to the accumulation of AGEs in tissues, but it is also associated with atherosclerosis, Alzheimer’s disease, end stage renal disease, rheumatoid arthritis, sarcopenia, cataracts, and other degenerative ophthalmic diseases, Parkinson’s disease, vascular dementia and several other chronic diseases [16,17,18,19]. For instance, Bar et al have demonstrated differential increases of AGEs products in Alzheimer’s dementia and vascular dementia compared to controls [20].…”
Section: Implications For Healthmentioning
confidence: 99%
“…The accumulation of AGEs in tissues may contribute to increased OS, and as a final result, impair organ function [16]. Indeed, within the complex the association between OS and aging ovarian follicles, AGEs may have an important role as they accumulate over the lifespan [71].…”
Section: Ages In the Elderlymentioning
confidence: 99%
“…PP are present in many edible plants and thus represent an integral part of human supply [19]. Several studies have shown that high regular intake of some phenolic compounds in the diet plays a preventive action against several human diseases, such as cardiovascular pathologies, atherosclerosis, osteoporosis, allergies, diabetes, neurodegenerative diseases and cancer [20], [21]. Although the mechanisms by which these natural compounds exert their benefits are not fully understood, anti-inflammatory effects of PP have been attributed primarily to their antioxidant activity, because they were known to scavenge and prevent the formation of reactive oxygen and nitrogen species (ROS and RNS, respectively) [22], [23], which represent important hallmarks of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, efforts have been made to identify immunological risk phenotypes in aged people, and proinflammatory phenotypes seem to predict unhealthy aging [63]. Use of nutraceuticals to prevent or arrest age-related diseases such as atherosclerosis has become very popular worldwide [64].…”
Section: Resultsmentioning
confidence: 99%